Introductory Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-805-X
ISBN 13: 978-0-13417-805-9

Chapter 6 - Section 6.5 - A General Factoring Strategy - Exercise Set - Page 463: 113



Work Step by Step

$ 10x^{2}(x+1)-7x(x+1)-6(x+1)\qquad$...factor out the common term, $(x+1)$ $=(x+1)(10x^{2}-7x-6)$ ... Searching for two factors of $ac=-60$ whose sum is $b=-7,$ we find$\qquad 5$ and $-12.$ Rewrite the middle term and factor in pairs: $=(x+1)(10x^{2}+5x-12x-6)=$ $=(x+1)[5x(2x+1)-6(2x+1)]$ =$(x+1)(2x+1)(5x-6)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.